Graves’ Disease Causing Pancytopenia and Autoimmune Hemolytic Anemia at Different Time Intervals: A Case Report and a Review of the Literature - Peyman Naji; Geetika Kumar; Shabana Dewani; William A. Diedrich; Ankur Gupta (Case Reports in Medicine)
Graves’ disease (GD) is associated with various hematologic abnormalities but pancytopenia and autoimmune hemolytic anemia (AIHA) are reported very rarely. Herein, we report a patient with GD who had both of these rare complications at different time intervals, along with a review of the related literature. The patient was a 70-year-old man who, during a hospitalization, was also noted to have pancytopenia and elevated thyroid hormone levels. Complete hematologic workup was unremarkable and his pancytopenia was attributed to hyperthyroidism. He was started on methimazole but unfortunately did not return for followup and stopped methimazole after a few weeks. A year later, he presented with fatigue and weight loss. Labs showed hyperthyroidism and isolated anemia (hemoglobin 7 g/dL). He had positive direct Coombs test and elevated reticulocyte index. He was diagnosed with AIHA and started on glucocorticoids. GD was confirmed with elevated levels of thyroid stimulating immunoglobulins and thyroid uptake and scan. He was treated with methimazole and radioactive iodine ablation. His hemoglobin improved to 10.7 g/dL at discharge without blood transfusion. Graves’ disease should be considered in the differential diagnosis of hematologic abnormalities. These abnormalities in the setting of GD generally respond well to antithyroid treatment.